2018
DOI: 10.1186/s12913-018-3185-8
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting out-of-pocket requirements: trends in spending, financial access barriers, and policy in ten high-income countries

Abstract: BackgroundCountries rely on out-of-pocket (OOP) spending to different degrees and employ varying techniques. The article examines trends in OOP spending in ten high-income countries since 2000, and analyzes their relationship to self-assessed barriers to accessing health care services. The countries are Australia, Canada, France, Germany, the Netherlands, New Zealand, Norway, Sweden, Switzerland, the United Kingdom, and the United States.MethodsData from three sources are employed: OECD statistics, the Commonw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 11 publications
3
66
1
2
Order By: Relevance
“…OOPCs can vary greatly by country, with countries with low public funding of healthcare costs (e.g. the United States) reporting higher OOPCs and more frequent reports of barriers to health service access (Rice et al, ). Furthermore, the costs of resources are highly variable across countries.…”
Section: Discussionmentioning
confidence: 99%
“…OOPCs can vary greatly by country, with countries with low public funding of healthcare costs (e.g. the United States) reporting higher OOPCs and more frequent reports of barriers to health service access (Rice et al, ). Furthermore, the costs of resources are highly variable across countries.…”
Section: Discussionmentioning
confidence: 99%
“…Current data from the World Bank show that 7% of the population in 110 countries spend up to 10% of their total consumption as OOPE for healthcare services. Those OOPEs stand in direct relation to healthcare access and hence represent an important barrier to healthcare use . Evidence indicates that even in case of partial user fee removal, the very poor and ill often cannot afford to pay for their treatment due to uncovered costs or have to sell assets in order to be able to do so .…”
Section: Introductionmentioning
confidence: 99%
“…As policies are implemented to reform health financing and service provision, the international community explicitly recognizes the need to monitor OOPE as an essential parameter against which to evaluate the progress being made toward Universal Health Coverage (UHC) . Several authors have argued in favor of measuring OOPE and its determinants even prior to the implementation of new UHC policies, as a means of generating baseline values against which to assess improvements in financial protection …”
Section: Introductionmentioning
confidence: 99%
“…This suggests overall lower cost-sharing requirements for hospital care than ambulatory care across health-care settings. [68][69][70] Our results also showed that nonmedical costs at destination and home country contributed considerably to the direct costs of dengue illness in travelers, averaging US$152 and US$171 per patient for hospitalization, and US$61 and US$79 per patient for ambulatory care, respectively.…”
Section: Discussionmentioning
confidence: 59%
“…Small sample size precluded an analysis and comparison of out-of-pocket medical spending for dengue illness by home country to account for the differences in the health-care systems, which affect cost-sharing requirements for a given basket of health services across countries. 68 Although most hospitalized patients reported having health insurance coverage for medical expenditures, they failed to reliably report on the received or anticipated reimbursement amount. This may be related to the factors associated with reimbursement processes depending on the type of health insurance, particularly for medical expenditures incurred abroad, including complex reimbursement requirements, lengthy processing wait times, and payment delays, all of which may even affect how many claims are successfully filed and accepted.…”
Section: Discussionmentioning
confidence: 99%